EVALUASI USABILITY TERHADAP ANTARMUKA WEBSITE DENGAN METODE HEURISTIC EVALUATION (Studi Kasus : Website Klinik Dentisari) - Aina Maulina Esa, (2020)
The study is conducted to evaluate the interface of the Dentisari Clinic website for identifying usability levels on the dentisari clinic website. In this study is evaluated by user and evaluator where users evaluate with usability attributes and evaluators Based on the nine principles developed by David Travis. Related to the heuristic evaluation method. Value derived from this study is both a user's evaluation and an evaluator's analysis to know usability that needs to be enhanced and corrected. Based on usability value memorability levels on the dentisari website of 78.8% and this can be stated well because it is easy to remember and the lowest percentage of satisfaction attributes is 64.3%. At the rate of assessments conducted by evaluators produced an 86% percent based on writing and content quality principles and the lowest results on search principles by 47%. The average level of usability on the Dentisari Clinic website can be identified both by a user's evaluation and with a evaluator's evaluation of only a few usability levels should be corrected and further improved for the next stage of development.